2019
DOI: 10.1038/s41436-018-0431-8
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6-guided opioid therapy improves pain control in CYP2D6 intermediate and poor metabolizers: a pragmatic clinical trial

Abstract: Purpose: CYP2D6 bioactivates codeine and tramadol, with intermediate and poor metabolizers (IMs and PMs) expected to have impaired analgesia. This pragmatic proof-of-concept trial tested the effects of CYP2D6-guided opioid prescribing on pain control. Methods: Participants with chronic pain (94% on an opioid) from 7 clinics were enrolled into CYP2D6-guided (n=235) or usual care (n=135) arms using a cluster design. CYP2D6 phenotypes were assigned based on genotype and CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 36 publications
2
121
0
2
Order By: Relevance
“…Oxymorphone, which is the second most abundant metabolite, exhibits 8 times the potency and 40 times the affinity on μ‐opioid receptor as compared to oxycodone. Despite this, the majority of studies suggest that the contribution of oxymorphone to the pharmacodynamic effects of oxycodone administrations is minimal, presumably attributed to the very low plasma concentrations, rapid glucuronidation to an inactive metabolite and/or the low rate of crossing the blood‐brain barrier . Nevertheless, opposing results have been demonstrated by Samer et al, although the impact on pupil size was not as substantial as other pharmacodynamic parameters, thus questioning the central effects of oxymorphone .…”
Section: Discussionmentioning
confidence: 97%
“…Oxymorphone, which is the second most abundant metabolite, exhibits 8 times the potency and 40 times the affinity on μ‐opioid receptor as compared to oxycodone. Despite this, the majority of studies suggest that the contribution of oxymorphone to the pharmacodynamic effects of oxycodone administrations is minimal, presumably attributed to the very low plasma concentrations, rapid glucuronidation to an inactive metabolite and/or the low rate of crossing the blood‐brain barrier . Nevertheless, opposing results have been demonstrated by Samer et al, although the impact on pupil size was not as substantial as other pharmacodynamic parameters, thus questioning the central effects of oxymorphone .…”
Section: Discussionmentioning
confidence: 97%
“…Despite calls for comparative effectiveness research in genomic medicine, the use of PCTs to develop this evidence base remains sparse . At present, the majority of genomic and precision medicine research has occurred within the early phases of the translational continuum (T0/T1), focusing primarily on gene discovery, support for analytic and clinical validity, and the development of health applications .…”
Section: Discussionmentioning
confidence: 99%
“…Despite calls for comparative effectiveness research in genomic medicine, 7,8 the use of PCTs to develop this evidence base remains sparse. 34,35 At present, the majority of genomic and precision medicine research has occurred within the early phases of the translational continuum (T0/T1), focusing primarily on gene discovery, support for analytic and clinical validity, and the development of health applications. 2,9 Although growing, very few research initiatives have been 22 Regular CVD risk score calculations refer to the daily generation of 10-year CVD risk scores using the birthday parity method as described by Vassy et al 21 CVD, cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…8 A clinical trial investigating the effects of CYP2D6-guided opioid prescribing on pain control found that intermediate and poor metabolizers prescribed genotype-appropriate doses of tramadol and/or codeine (n = 45) had greater improvement of pain intensity in the CYP2D6-guided versus usual care arm. 9 Our own investigations of patient response related to codeine, tramadol, hydrocodone, and oxycodone in a cohort of 257 patients found that more than 30% of those with a CYP2D6 poor or ultra-rapid phenotype experienced either adverse reactions or lack of pain relief related to opioid use. 10 In short, these results suggest poor pain control in individuals with CYP2D6 poor metabolizer status and more adverse reactions in individuals with CYP2D6 ultra-rapid metabolizer status.…”
Section: Introductionmentioning
confidence: 99%